Hegemoni tentara - Azca, M. Najib ([Yogyakarta] : LKiS, 1998)
Socio-political functions of Angkatan Bersenjata Republik Indonesia, the Indonesian Armed Forces.
Based on the author's thesis (S1).
Includes bibliographical references (p. 265-271) and index.
Keywords: Indonesia. -- Angkatan Bersenjata -- Political activity; Indonesia. -- Angkatan Bersenjata -- Civic action; Indonesia -- Armed Forces -- Political activity; Indonesia -- Armed forces -- Civic action